2017
DOI: 10.1007/s11250-017-1239-2
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomiasis challenge estimation using the diminazene aceturate (Berenil) index in Zebu in Gabon

Abstract: A longitudinal study was conducted within a cattle ranch in Gabon to determine the diminazene aceturate (Berenil) index (DAI) in a group of Zebu, raised under low tsetse density; this measure providing an assessment of trypanosomiasis risk. The objective was to evaluate the trypanosomiasis pressure thus informing trypanosomiasis control methods and cattle management. Twenty female adult Zebu were monitored for 24 weeks during the dry season. Blood samples were collected on a weekly basis and subjected to paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Additionally, an earlier survey conducted in cattle maintained under traditional management system in 8 villages in Hawagelan district, western Ethiopia ( Bekele & Nasir, 2011 ) revealed that the mean PCV of trypanosome-infected animals was significantly lower than that of non-infected animals. Lower herd average PCVs for trypanosome-positive cattle compared to trypanosome-negative cattle have also been reported in Ankole cattle in Uganda ( Waiswa & Katunguka-Rwakishaya, 2004 ), Angoni cattle in Zambia ( Marcotty et al , 2008 ), Doayo and Zebu White Fulani cattle in Cameroun ( Achukwi & Musongong, 2009 ) and Zebu cattle in Gabon ( Cossic et al , 2017 ). In Nigeria, Ohaeri & Eluwa (2011) observed that in addition to cattle, other domestic ruminants that were naturally infected with trypanosomes had significantly lower ( p < 0.05) PCV and RBC counts compared to uninfected animals.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, an earlier survey conducted in cattle maintained under traditional management system in 8 villages in Hawagelan district, western Ethiopia ( Bekele & Nasir, 2011 ) revealed that the mean PCV of trypanosome-infected animals was significantly lower than that of non-infected animals. Lower herd average PCVs for trypanosome-positive cattle compared to trypanosome-negative cattle have also been reported in Ankole cattle in Uganda ( Waiswa & Katunguka-Rwakishaya, 2004 ), Angoni cattle in Zambia ( Marcotty et al , 2008 ), Doayo and Zebu White Fulani cattle in Cameroun ( Achukwi & Musongong, 2009 ) and Zebu cattle in Gabon ( Cossic et al , 2017 ). In Nigeria, Ohaeri & Eluwa (2011) observed that in addition to cattle, other domestic ruminants that were naturally infected with trypanosomes had significantly lower ( p < 0.05) PCV and RBC counts compared to uninfected animals.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, an earlier survey conducted in cattle maintained under traditional management system in 8 villages in Hawagelan district, western Ethiopia ( Bekele & Nasir, 2011) revealed that the mean PCV of trypanosome-infected animals was significantly lower than that of non-infected animals. Lower herd average PCVs for trypanosome-positive cattle compared to trypanosome-negative cattle have also been reported in Ankole cattle in Uganda ( Waiswa & Katunguka-Rwakishaya, 2004), Angoni cattle in Zambia ( Marcotty et al , 2008), Doayo and Zebu White Fulani cattle in Cameroun ( Achukwi & Musongong, 2009) and Zebu cattle in Gabon ( Cossic et al , 2017). In Nigeria, Ohaeri & Eluwa (2011) observed that in addition to cattle, other domestic ruminants that were naturally infected with trypanosomes had significantly lower ( p < 0.05) PCV and RBC counts compared to uninfected animals.…”
Section: Discussionmentioning
confidence: 80%
“…In Nigeria, domestic ruminants that were naturally infected with trypanosomes had significantly lower (p<0.05) PCV and RBC counts compared to uninfected animals [36]. Lower herd average PCVs for trypanosomepositive cattle compared to trypanosome-negative cattle have also been reported from Ghana [37], Zambia [32], Cameroon [38] and Gabon [39].…”
Section: Discussionmentioning
confidence: 99%